Revitalisasi Pendidikan Karakter Berbasis Sufiisme Merespon Era Revolusi Industri 4.0 - Abdul Malik Usman (SALIHA: Jurnal Pendidikan & Agama Islam, 2019)
Character education as education in general, as an effort to incorporate values into students to shape the character, character and noble character (noble character), is now increasingly gaining a place in the process of organizing education in the country, even as a national movement in momentum of National Education Day May 20 2011 commemoration by the President of the Republic of Indonesia along with relevant ministers. This is a step forward and anticipated in response to the development of modernization, industrialization and globalization in the era of industrial revolution 4.0. Sufism (Sufism) as one aspect of Islamic teachings whose focus is on the development of esoteric aspects becomes the foundation of strengthening character education, in addition to guiding humanity to fulfill spiritual thirst, in the midst of a wave of disorientation in the values and emptiness of souls that infect life.